Severe fetal anemia and hydrops fetalis associated with compound heterozygosity for Hb Zurich-Albisrieden (:c.178G>C) and Hb Quong Sze (:c.377T>C) - Li Du (Journal of International Medical Research, 2021)
We report on a fetus with cardiomegaly and increased middle cerebral artery-peak systolic velocity at 25 weeks of gestation. Severe fetal anemia (hemoglobin (Hb) level 37 g/L) was confirmed by cordocentesis. Hb analysis showed that Hb Bart’s was 9% in cord blood. Molecular analysis of the proband’s family found that the mother was a carrier of Hb Quong Sze (Hb QS, HBA2 :c.377T>C), the father was a carrier of Hb Zurich-Albisrieden (Hb ZA, HBA2 :c.178G>C), and the fetus was a compound heterozygote for Hb ZA and Hb QA. Despite intrauterine blood transfusions, the fetus experienced problems including oligohydramnios, growth retardation, placental thickening, and heart enlargement in the third trimester. The couple chose to terminate the pregnancy, and fetal autopsy confirmed the above diagnosis. This is the first report of a case of Hb ZA compounded with Hb QS, and provides a reference for genetic counselling and prenatal diagnosis in the Chinese population.